Diabetic Retinopathy and Regulation of Mitochondrial Glutathione-Glutathione Peroxidase Axis in Hyperhomocysteinemia - Pooja Malaviya; Renu A. Kowluru (MDPI AG, 2024)
Diabetic patients have elevated homocysteine levels, and hyperhomocysteinemia is shown to exacerbate mitochondrial damage, which plays a central role in diabetic retinopathy. Glutathione peroxidases (GPx) catalyze hydrogen peroxide (H2O2) reduction using glutathione (GSH) as a cofactor. GSH and GPx are mainly cytosolic but are also present in the mitochondria to neutralize H2O2 produced by superoxide dismutase, and in diabetes, they are downregulated. Hyperhomocysteinemia also disrupts the balance between S-adenosyl-L-homocysteine and S-adenosylmethionine (SAM); SAM is also a methyl donor for DNA methylation. The aim of this study was to investigate the role of homocysteine in mitochondrial GSH-GPx1 regulation in diabetic retinopathy. Human retinal endothelial cells in 20 mM D-glucose + high homocysteine were analyzed for ROS, GSH and GPx in the mitochondria, and SAM levels and GPx1 promoter DNA methylation were also studied (5-methylcytosine and MS-PCR). The results were confirmed in the retina from streptozotocin-induced hyperhomocysteinemic (cystathionine-β-synthase-deficient) diabetic mice. High homocysteine exacerbated the glucose-induced decrease in GSH levels and GPx activity in the mitochondria and the downregulation of GPx1 transcripts and further increased SAM levels and GPx1 promoter DNA methylation. Similar results were obtained in a hyperglycemic-hyperhomocysteinemic mouse model. Thus, elevated homocysteine in diabetes hypermethylates GPx1 promoter, thus decreasing the mitochondrial GPx/GSH pool and exacerbating mitochondrial damage. Modulating hyperhomocysteinemia could be a potential therapeutic avenue to target mitochondrial dysfunction in diabetic retinopathy.